Rye Pm8 and wheat Pm3 are orthologous genes and show evolutionary conservation of resistance function against powdery mildew. (5th November 2013) - Hurni, Severine; Brunner, Susanne; Buchmann, Gabriele; Herren, Gerhard; Jordan, Tina; Krukowski, Patricia; Wicker, Thomas; Yahiaoui, Nabila; Mago, Rohit; Keller, Beat
Summary The improvement of wheat through breeding has relied strongly on the use of genetic material from related wild and domesticated grass species. The 1RS chromosome arm from rye was introgressed into wheat and crossed into many wheat lines, as it improves yield and fungal disease resistance. Pm8 is a powdery mildew resistance gene on 1RS which, after widespread agricultural cultivation, is now widely overcome by adapted mildew races. Here we show by homology‐based cloning and subsequent physical and genetic mapping that Pm8 is the rye orthologue of the Pm3 allelic series of mildew resistance genes in wheat. The cloned gene was functionally validated as Pm8 by transient, single‐cell expression analysis and stable transformation. Sequence analysis revealed a complex mosaic of ancient haplotypes among Pm3‐ and Pm8‐like genes from different members of the Triticeae. These results show that the two genes have evolved independently after the divergence of the species 7.5 million years ago and kept their function in mildew resistance. During this long time span the co‐evolving pathogens have not overcome these genes, which is in strong contrast to the breakdown of Pm8 resistance since its introduction into commercial wheat 70 years ago. Sequence comparison revealed that evolutionary pressure acted on the same subdomains and sequence features of the two orthologous genes. This suggests that they recognize directly or indirectly the same pathogen effectors that have been conserved in the powdery mildews of wheat and rye.